A Qualitative Process Evaluation and Quality Improvement of a State Drug Overdose Reporting System Data Collection Approach - Mircea Lazar PhD; Joshua Jayasundara MA, MES; Jessica Korona-Bailey MPH; Sutapa Mukhopadhyay PhD (SAGE Publishing, 2024)
Tennessee registered the second-highest drug overdose mortality rate of any state in 2022; such deaths have grown by 90% from 2019 to 2022. Tennessee has participated in the State Unintentional Drug Overdose Reporting System (SUDORS) since 2018. An abstraction team synthesizes data for SUDORS from death certificates, autopsies, and other sources. The purpose of this study was to engage in a comprehensive qualitative evaluation of our SUDORS process to distill insights that could improve abstraction speed and quality while reducing abstractor burnout. We conducted 2 rounds of interviews and focus groups with all 7 members of the Tennessee abstraction team in late 2023 and early 2024. The researcher asked questions regarding the adequacy of the current project management approach and team communication level, abstractors' stress levels, the need for further training, and whether additional data science-based tools could be deployed to increase the speed and accuracy of abstraction. The study yielded several actionable insights for improving abstraction capacity and lessening stress burdens. Accordingly, we made changes to our project management, team communication, and training approaches; worked to better integrate our extant data science tools; and took steps to improve mental well-being. As a result, the average time it takes for an abstractor to enter a case into the NVDRS platform dropped from 12.2 to 6.5 minutes, and all team members noted a decrease in stress levels. The changes made as a result of the findings of this study will help the State keep pace with a high case load and will support abstractors' mental well-being.